Matrix effects on the magnetic properties of a molecular spin triangle embedded in a polymeric film - Tesi, Lorenzo; Boudalis, Athanassios K; Drerup, Katja; Ruben, Mario; van Slageren, Joris (Physical chemistry chemical physics : PCCP, 2024)
Molecular triangles with competing Heisenberg interactions and significant Dzyaloshinskii-Moriya interactions (DMI) exhibit high environmental sensitivity, making them potential candidates for active elements for quantum sensing. Additionally, these triangles exhibit magnetoelectric coupling, allowing their properties to be controlled using electric fields. However, the manipulation and deposition of such complexes pose significant challenges. This work explores a solution by embedding iron-based molecular triangles in a polymer matrix, a strategy that offers various deposition methods. We investigate how the host matrix alters the magnetic properties of the molecular triangle, with specific focus on the magnetic anisotropy, aiming to advance its practical applications as quantum sensors.